Information and perioperative education of cardiac surgery patients - Vastardis, L; Diakomopoulou, Eleni; Kalogianni, A; Pistolas, Dimitrios; Argiriou, M; Apostolakis, Efstratios; Merkouris, Anastasios (My University, 2001)
Today, in a turbulent and competitive health care environment patients more and more, seek to learn what is happening in their own situation and participate in planning their health care and decision-making. Cardiac surgery patients are discharged earlier and anticipate many problems during the rehabilitation period. Preoperative and postoperative education of the patients is of great importance and patients knowledge of self care after discharge is a main outcome indicator of the quality of the provide services. The aim of this study was to assess cardiac surgery patients’ knowledge of self care after the discharge and explore any correlation with the patient characteristics. The sample consisted of 91 patients who admitted during 3 months in two cardiac surgery wards and had an open-heart operation. A special questionnaire was developed based on four dimensions: general, diet, rest, and drugs. Patients scored higher the diet scale (mean=1,91, SD=0,26, scale 0-2) and lower the drug scale ( mean=0,10, SD=0,4, scale 0-2). The majority of the patients wanted to learn more (98,9%) and nurses had not been involved in the educational process. The analysis of variance revealed an indication of correlation between the educational level and the patients’ knowledge but the small sample does not allow safe conclusions. The results can be used for the planning of the patients’ preoperative and postoperative education.